A química do solo: revisão bibliográfica e principais métodos de investigação agronômica - Lima Filho, Mauro Henrique de (Universidade Federal de São Carlos, 2022)
Throughout human history, agriculture figures prominently among economic activities. The notion that productivity in the field is conditioned to environmental factors is as old as the activity itself, but what we now call “an open-air industry” was the subject of intense investigation over the centuries, until a scientific basis was consolidated to substantiate human intervention on a scale never before experienced. The 19th century marks the history of Europe for its political, scientific and cultural events, and it is there that the foundations of the agronomic sciences reside, as well as the first industrial enterprises of agricultural inputs; the demand for productivity in the fields is driven by the economic model of an industrial society of mass production. The impact of this advent is crucial, so that nations with limitations in the expansion of their agricultural frontier could meet the demands of an increasingly numerous population. From the discoveries on plant nutrition, efforts began to target methods of quantification of these nutrients in soils, and their dynamics in incorporation by crops. It is during the 20th century that the methods of extraction and quantification of nutrients in soils are consolidated, which are widely used nowadays, so that laboratories around the world generate analytical information about the quality of a soil, providing a basis for an agronomic intervention; this is what we have come to call today as precision agriculture. This work proposes to trace a brief history of the plant nutrition concept, and to reference the theory and practice of modern methods applied in a chemical laboratory of soil fertility.
The soil chemistry: bibliographic review and main methods of agronomic research
Keywords: Agricultura; Agronomia; Nutrição vegetal; Solos; Química; CIENCIAS EXATAS E DA TERRA::QUIMICA